2017
DOI: 10.1111/1477-9552.12220
|View full text |Cite
|
Sign up to set email alerts
|

Price and Volatility Transmission and Market Power in the German Fresh Pork Supply Chain

Abstract: We investigate the relationship between the transmission of price volatility and market power in the German fresh pork supply chain. We use a theoretical model underpinning this relationship followed by an empirical application that uses monthly farm, slaughterhouse and retail pork price data for the period 2000–2011. We examine both the relationships of market power with price level transmission and price volatility transmission in the chain. We use a vector error correction model and least squares regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…One of the primary ways by which shock propagation along supply chains has been examined in the literature is through the effects of disruptions on prices. Price transmission across supply chains informs economic decisions at various stages, but volatile prices can create uncertainty for downstream supply chain actors 53 . The effect of transmission along a supply chain depends on the structure of the sector and the policy context.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the primary ways by which shock propagation along supply chains has been examined in the literature is through the effects of disruptions on prices. Price transmission across supply chains informs economic decisions at various stages, but volatile prices can create uncertainty for downstream supply chain actors 53 . The effect of transmission along a supply chain depends on the structure of the sector and the policy context.…”
Section: Resultsmentioning
confidence: 99%
“…Foods with multiple sourcing options, substitute products and longer shelf lives can better buffer supply and dampen variability 54,55 . Concentrated market power also restricts price transmission when retailers exercise their power to keep consumer prices stable during volatile periods 53 . Conversely, foods with few substitutes, foods requiring longer grow-out periods, sectors with fewer industry actors and regions with limited infrastructure tend to have lower capacity to dampen supply or price variability, resulting in greater propagation along the supply chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller and Hayenga (2001) showed that changes in wholesale prices are asymmetrically transmitted to retail prices in relatively low‐frequency cycles, and that wholesale pork prices adjust asymmetrically to changes in farm prices at all frequencies. Assefa et al (2017) used a vector error correction model (VECM) to analyze price transmission in vertical German pork markets, presenting evidence of asymmetric price transmission. Yet Bakucs and Ferto (2005) found symmetric transmission between farm price and retail price in the Hungarian pork market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both studies provided a comparative analysis of the behavior of price dynamics in levels of the quality-differentiated product and its conventional counterpart. Third, despite the growing importance of the analysis of price volatility through the supply chain, this issue has been limited to non-protected food products, with scarce country and product coverage ( [27,28] in the agrifood sector and [29,30] in the seafood sector), but has not covered food-quality-labeled products so far.…”
Section: Introductionmentioning
confidence: 99%